ANALISIS FAKTOR-FAKTOR YANG MENENTUKAN ELASTISITAS PERMINTAAN AYAM POTONG DI KOTA TIMIKA - Hariyanto Hariyanto; SISKA SISKA; Antje Tuasela (CV. Adiba Aisha Amira, 2025)
This study aims to determine the factors that determine the elasticity of demand for broiler chicken in Timika City. The research method used is a descriptive method. In this study, the data collection technique used is a questionnaire. To determine the factors that determine the elasticity of demand for broiler chicken in Timika City, the analysis instrument used is Confirmatory Factor Analysis (CFA). The results of this study indicate that out of 5 factors, there are only 3 most dominant factors. These factors are the taste or taste factor of the community with a correlation value of -0.762, the price factor of the goods themselves with a correlation value of 0.721 and the estimated price factor in the future with a correlation value of 0.535.